2016
DOI: 10.1177/1740774516646578
|View full text |Cite
|
Sign up to set email alerts
|

Statistical lessons learned for designing cluster randomized pragmatic clinical trials from the NIH Health Care Systems Collaboratory Biostatistics and Design Core

Abstract: Background/Aims Pragmatic clinical trials embedded within health care systems provide an important opportunity to evaluate new interventions and treatments. Networks have recently been developed to support practical and efficient studies. Pragmatic trials will lead to improvements in how we deliver health care and promise to more rapidly translate research findings into practice. Methods The NIH Health Care Systems Collaboratory was formed to conduct pragmatic clinical trials and to cultivate collaboration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
81
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 37 publications
0
81
0
1
Order By: Relevance
“…In our running example, we would be interested in testing whether the treatment effect differs between two different racial groups. Based on the linear mixed effects model (4), the scaled GLS estimator √ n(̂4 − 4 ) is asymptotically normal with mean zero and variance equal to the lower right element of Σ = lim n→∞ nΣ n , which we denote by 2 4 . This suggests the use of the z-test statistic, √ n̂4∕̂4, which will be referenced to the standard normal distribution.…”
Section: Basic Setting With One Covariatementioning
confidence: 99%
See 2 more Smart Citations
“…In our running example, we would be interested in testing whether the treatment effect differs between two different racial groups. Based on the linear mixed effects model (4), the scaled GLS estimator √ n(̂4 − 4 ) is asymptotically normal with mean zero and variance equal to the lower right element of Σ = lim n→∞ nΣ n , which we denote by 2 4 . This suggests the use of the z-test statistic, √ n̂4∕̂4, which will be referenced to the standard normal distribution.…”
Section: Basic Setting With One Covariatementioning
confidence: 99%
“…x and the two ICC parameters y|x and x . Compared with the conventional CRT powered to test for the overall treatment effect, we require information of the adjusted outcome ICC, and information of X ij through two second-order parameters 2 x and x . The above expression allows us to study the relationship between sample size and distributions of X ij .…”
Section: Basic Setting With One Covariatementioning
confidence: 99%
See 1 more Smart Citation
“…Members of the Collaboratory Core Groups (described in more detail below) worked with the PIs to facilitate the PCTs and have reported on solutions to the challenges encountered. These include a special issue on the ethics of research in usual care settings [ 17 , 18 ], a special issue on the ethical and regulatory complexities of pragmatic clinical trials [ 15 , 19 – 29 ], journal articles on initiating and implementing patient-reported outcomes measures [ 30 ], electronic health records, phenotyping, and informatics [ 31 – 33 ], stakeholder engagement and health care systems interactions [ 34 – 37 ], as well as biostatistical lessons learned on cluster and constrained randomization [ 38 , 39 ]. Members of the Collaboratory have also developed a Living Textbook on the design, conduct, and dissemination of PCTs ( http://rethinkingclinicaltrials.org/ ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet pragmatic trials also introduce several methodological challenges [8][9][10][11][12][13]. One major challenge in pragmatic cluster-randomized trials occurs when participants are identified after randomization, as in open-cohort or continuous recruitment designs [14][15][16].…”
Section: Introductionmentioning
confidence: 99%